DISCOURSE AND TECHNOLOGY: INFORMATIONAL PRACTICES OF THE ASSURINÍ INDIGENOUS PEOPLES OF TROCARÁ. - Pinto, Benedita Celeste de Moraes; Domingues, Andrea Silva; Moreira, Cristian Caio Silva (Revista de Letras, 2024)
This study aimed to analyze how the use of communication technologies occurs among the Asuriní indigenous people of Aldeia Trocará, in the municipality of Tucuruí, Pará, observing possible changes in the daily lives of the inhabitants of this territory from the interaction in social networks and the use of technological devices. Methodologically, we carried out a qualitative study, with research of / in the field which involved strategies with the use of technology in a pandemic period and exchange of knowledge with collaborators, research subjects; this moment allowed us a corpus of analysis composed of oral narratives and photographs. Theoretically, we are affiliated with a Critical Social History, with a political and historical perspective always based on research ethics. As part of the results, it was possible to perceive that the Asuriní indigenous people of Aldeia Trocará have been using ICTs as a way of acquiring new knowledge and resistance in the face of the needs that are presented in the current globalized world.